Analisis Faktor Penyebab Minimnya Minat Masyarakat Kabupaten Rejang Lebong Menjadi Mahasiswa Prodi Ekonomi Syariah IAIN Curup - Muhammad Istan; Ratih Komala Dewi (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2020)
Sharia Economic Study Program of Curup State Islamic University (IAIN Curup) has obtained the Operating Permit from 2016. Based on the data obtained by students enrolled in the Islamic economics study program, only a minority came from Rejang Lebong district, while the majority came from outside the region.The purpose of this study is to determine whether there is an influence of knowledge about the institution towards the lack of community interest in Rejang Lebong Regency to study at the Curriculum of Islamic Studies Program IAIN Curup. The research data collection methods were questionnaires and interviews, with 334 respondents from 12th grade high school students in the Rejang Lebong district selected randomly and analyzed using the Fish Bone method. The results showed that the low interest of the community to continue their education to the Curriculum of Islamic Studies program IAIN Curup due to lack of knowledge about the existence and the existence of scholarships, supporting facilities, qualifications of lecturers in the Curriculum of Islamic Studies Program IAIN Curup, lack of information dissemination about the process of admission of new students in the Economic Study Program Syariah IAIN Curup, not yet evenly distributed participants of the vision and mission of IAIN Curup Sharia Economic Study Program.